Reproductive phenology of Euterpe edulis (Arecaceae) along a gradient in the Atlantic rainforest of Brazil - Castro, E. R.; Galetti, M.; Morellato, L. P. C. (CSIRO Publishing, 2007)
The palm Euterpe edulis Mart. is one of the dominant tree species in the Atlantic rainforest and considered a key resource for many frugivorous birds. We compared the reproductive phenology of E. edulis in three types of Atlantic rainforest (two lowland forests, restinga and coastal-plain, and a premontane forest) on Cardoso Island (Cananeia, São Paulo, Brazil), aiming to answer the following questions: (i) whether the reproduction of E. edulis is annual and seasonal across the years in the three forest types studied; (ii) what are the environmental factors influencing the reproductive phenology of E. edulis; and (iii) how does the timing of fruiting and fruit production of E. edulis vary among the three forest types? We evaluated the presence of flowers and fruits (immature, unripe and ripe) from August 2001 to July 2004 in 150 individuals (50 per forest), and estimated the number of infructescences with ripe fruits and the production of fruits and seeds by collecting them on the forest floor in the three forest types. Flowering and fruiting of E. edulis were annual and significantly seasonal in the three forest types, with a high synchrony of flowering and medium to low synchrony of fruiting. Flowering peaked in November and December, and immature and unripe fruits peaked in January and March, all during the rainy season. Immature and unripe fruit phases were correlated with the daylength, precipitation and temperature, important factors for fruits development. Ripe fruits peaked in April and May, in the less rainy season, with significant differences in the mean dates among forests. The number of infructescences with ripe fruits and the biomass of fruits and seeds collected on the ground also differed significantly among the forest types, being greater in the restinga and coastal plain forests, respectively. Differences in productivity were related to palm density in each area and the soil fertility. The complementary fruiting pattern of E. edulis in the forests studied may affect the distribution and abundance of certain frugivorous bird species that feed on their fruits.